Metabolism of azo dyes, methyl red and methyl orange by plants - Kamat, Rohit B.; Davis, Lawrence C. (My University, 2011)
Azo dyes like methyl red and methyl orange are known to be major human carcinogens besides being water pollutants. These dyes are still a cause of concern in the developing nations due to their unrestricted usage. Laccases and peroxidases isolated from bacteria and fungi are presently being explored for decolorizing dyes. Whole plants have rarely been employed in degrading dyes. The goal of our work is to identify and characterize the groups of enzymes from plants involved in the breakdown of dyes. Hydroponically cultivated Arabidopsis thaliana were treated with 20 mg/L solutions of methyl red and methyl orange prepared at two pH values, 4.6 and 6.3 in the presence or absence of external hydrogen peroxide. Presence of peroxide at either pH does not accelerate the decolorization of the dyes. Plants assayed at pH 4.6 (methyl red-4.5 nmoles/hr; methyl orange-3.9 nmoles/hr) were found to degrade the dyes at the same rate as that observed for pH 6.3 (methyl red-4.2 nmoles/hr; methyl orange-3.5 nmoles/hr). Within three days the plants were able to decolorize 60% of both the dyes. A strong salt, 0.1M magnesium sulphate, has been found to extract nearly 30% of the total enzyme activity measured by ABTS [2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid)] and peroxide at either pH. The peroxidase activity as measured by ABTS color reaction is in ~1000 fold excess over observed degradation of methyl red or methyl orange. This suggests that the enzymes involved in the dye uptake might have low substrate affinity, or low reactivity with the dyes.
Keywords: Azo dyes; Laccase; Peroxidase; Peroxidase; ABTS